2007
DOI: 10.1016/j.contraception.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study to compare the absorption and tolerability of two doses of levonorgestrel following single vaginal administration of levonorgestrel in Carraguard® gel: a new formulation for “dual protection” contraception

Abstract: Objective: The study was conducted to assess levonorgestrel (LNG) serum levels achieved after a single administration of two different doses of Carraguard vaginal gel containing LNG (CARRA/ LNG), designed for use as microbicide and contraceptive for potential dual-protection. Materials and methods:This was a randomized double-blind pharmacokinetic study conducted in 12 subjects enrolled at two centers. Each subject received a single vaginal administration of CARRA/LNG containing either 0.75 or 1.5 mg LNG per 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…One of the possible uses of this gel would be a pre-coital emergency contraceptive, for application before occasional intercourse. A recent pharmacokinetic study with CARRA/LNG containing 1.5 or 0.75 mg of levonorgestrel in 4 mL of gel, confirmed the vaginal absorption of this steroid [10]. LNG serum levels in the range known to interfere with the ovulatory process were achieved, thereby confirming the potential of CARRA/LNG gel as a new candidate product that could provide dual protection, both for prevention of pregnancy as well as prevention of STI.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…One of the possible uses of this gel would be a pre-coital emergency contraceptive, for application before occasional intercourse. A recent pharmacokinetic study with CARRA/LNG containing 1.5 or 0.75 mg of levonorgestrel in 4 mL of gel, confirmed the vaginal absorption of this steroid [10]. LNG serum levels in the range known to interfere with the ovulatory process were achieved, thereby confirming the potential of CARRA/LNG gel as a new candidate product that could provide dual protection, both for prevention of pregnancy as well as prevention of STI.…”
Section: Introductionmentioning
confidence: 76%
“…Mean serum LNG levels on days 1-5 after treatment with the single oral 0.75 mg dose in the Croxatto et al study [12] were between 30 and 60% higher than those observed in the present study after administration of the same dose via CARRA/LNG gel. Furthermore, pharmacokinetic studies indicate that the high peak that occurs 1-2 h after oral administration is missing after the administration of the vaginal gel [10,[14][15][16]. A lower Cmax and a later Tmax have similarly been reported with the vaginal route as compared with oral route of administration of LNG emergency contraceptive pills [17][18][19].…”
Section: Discussionmentioning
confidence: 96%
“…Maximum serum levels between 3.5 and 22.01 nmol/L were attained at 4–12 h following application confirming the vaginal absorption of this steroid [12]. …”
Section: Introductionmentioning
confidence: 90%
“…The ingredient is the carrageenan, PDR98 --15, which belongs to the sulfated polysaccharide class of compounds and has been shown to have in vitro antiviral and antibacterial properties against HIV, herpes simplex virus type 2 and Neisseria gonorrhoeae [70][71][72][73]. CARRA was tested to assess the use as a vehicle for the vaginal delivery of LNG with the dual purpose of preventing pregnancy and sexually transmitted infections.…”
Section: Vaginal Gelmentioning
confidence: 99%
“…In one study [71] conducted with 12 women, two CAR-RA--LNG gel formulations containing either 0.75 or 1.5 mg of LNG/4 ml of gel were evaluated and compared with respect to LNG absorption and clearance rates. Each woman used a single vaginal administration of CARRA--LNG containing one of the two doses on days 10 --12 of the menstrual cycle.…”
Section: Vaginal Gelmentioning
confidence: 99%